Wealth, mother's education and physical access as determinants of retail sector net use in rural Kenya. - Noor, A; Omumbo, J; Amin, A; Zurovac, D; Snow, R (2006)
BACKGROUND: Insecticide-treated bed nets (ITN) provide real hope for the reduction of the malaria burden across Africa. Understanding factors that determine access to ITN is crucial to debates surrounding the optimal delivery systems. The influence of homestead wealth on use of nets purchased from the retail sector is well documented, however, the competing influence of mother's education and physical access to net providers is less well understood. METHODS: Between December 2004 and January 2005, a random sample of 72 rural communities was selected across four Kenyan districts. Demographic, assets, education and net use data were collected at homestead, mother and child (aged < 5 years) levels. An assets-based wealth index was developed using principal components analysis, travel time to net sources was modelled using geographic information systems, and factors influencing the use of retail sector nets explored using a multivariable logistic regression model. RESULTS: Homestead heads and guardians of 3,755 children < 5 years of age were interviewed. Approximately 15% (562) of children slept under a net the night before the interview; 58% (327) of the nets used were purchased from the retail sector. Homestead wealth (adjusted OR = 10.17, 95% CI = 5.45-18.98), travel time to nearest market centres (adjusted OR = 0.51, 95% CI = 0.37-0.72) and mother's education (adjusted OR = 2.92, 95% CI = 1.93-4.41) were significantly associated with use of retail sector nets by children aged less than 5 years. CONCLUSION: Approaches to promoting access to nets through the retail sector disadvantage poor and remote communities where mothers are less well educated.